Congenital and neonatal malaria in a rural Kenyan district hospital: An eight-year analysis - Kager Piet; Berkley James A; Mturi Florence N; Talbert Alison W; Mwaniki Michael K; Marsh Kevin; Newton Charles R (Malaria Journal, 2010)
Abstract Background Malaria remains a significant burden in sub-Saharan Africa. However, data on burden of congenital and neonatal malaria is scarce and contradictory, with some recent studies reporting a high burden. Using prospectively collected data on neonatal admissions to a rural district hospital in a region of stable malaria endemicity in Kenya, the prevalence of congenital and neonatal malaria was described. Methods From 1st January 2002 to 31st December 2009, admission and discharge information on all neonates admitted to Kilifi District Hospital was collected. At admission, blood was also drawn for routine investigations, which included a full blood count, blood culture and blood slide for malaria parasites. Results Of the 5,114 neonates admitted during the eight-year surveillance period, blood slide for malaria parasites was performed in 4,790 (93.7%). 18 (0.35%) neonates with Plasmodium falciparum malaria parasitaemia, of whom 11 were admitted within the first week of life and thus classified as congenital parasitaemia, were identified. 7/18 (39%) had fever. Parasite densities were low, ≤50 per μl in 14 cases. The presence of parasitaemia was associated with low haemoglobin (Hb) of <10 g/dl (χ2 10.9 P = 0.001). The case fatality rate of those with and without parasitaemia was similar. Plasmodium falciparum parasitaemia was identified as the cause of symptoms in four neonates. Conclusion Congenital and neonatal malaria are rare in this malaria endemic region. Performing a blood slide for malaria parasites among sick neonates in malaria endemic regions is advisable. This study does not support routine treatment with anti-malarial drugs among admitted neonates with or without fever even in a malaria endemic region.